Correlation Between The Quality Of Education Services with Satisfaction Of Health Polytechnic Student Health Ministry Semarang 2013 - Hermien Nugraheni; Enik Sulistyowati; Triana Sri Hardjanti (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2014)
The purpose of this study was to explore the correlation between the quality of educational services with the student's satisfaction in Ministry of Health Polytechnic Semarang. It is a descriptive study with cross-sectional design (cross-sectional). Independent and dependent variables were measured at the same time. The research variables include the quality of education services and student satisfaction in the Ministry of Health Health Polytechnic Semarang. The result shows that the average students feel quite satisfied and satisfied with the educational services of Ministry of Health Polytechnic Semarang which includes: lecturer's appearance, educational administration, public facilities, libraries, laboratories and security system. The average point of Student's Perceptions about the Quality of Educational Services in Ministry of Health Polytechnic Semarang's ranges from quite suitable to appropriate. Test results with a statistical significance level of 5% proved that there is a correlation between Quality of Educational Service and Student's Satisfaction in Ministry of Health Polytechnic Semarang in general. However, based on bivariate analysis, there is no correlation between Quality of Educational Service and Student's Satisfaction for D III Dental Nursing, D IV Engineering Radiology and Obstetrics Semarang program.